General issues of the exercise of jurisdiction in the process of application of law enforcement measures at sea - A. P. Glazova (Московский журнал международного права, 2020)
INTRODUCTION. Currently, states can apply a whole range of law enforcement measures at sea in order to prevent such unlawful phenomena as piracy, slave trade, drug trafficking, migrant smuggling, etc. However, the problem of the exercise of jurisdiction by states within various maritime areas is the main sticking point during the implementation of these measures. In an attempt to exercise the law enforcement function at sea, the state can't ignore the fact that its ability to create legal norms and ensure their effective implementation depends not only on its will as a sovereign, but also on the restrictions imposed by international law. Therefore, maintaining a balance between limiting the “territorialization” of maritime areas and the need to carry out a law enforcement function logically entails the need to determine the nature and content of the concept of “jurisdiction of the state” within different maritime areas, as well as to identify specific features of this legal category. The present article focuses on this and other related issues.MATERIALS AND METHODS. Historical and comparative analysis along with dogmatic research approach were used in the research process and the entire research is well grounded in focusing on the norms of international treaty law and customary law. In addition to that this research focuses on the norms of national law governing issues related to the application of law enforcement measurement at the sea. Apart from those given material and methodical inputs, the doctrinal works of the relevant jurists have been used in this research.RESEARCH RELULTS. The author comes to an alternative conclusion that territorial jurisdiction within the maritime territory is not absolute, which is due, apparently, the principle of freedom of the high seas which have a longer support by the international community. The definition of jurisdiction as extraterritorial is not self-sufficient, since in case of conflict of jurisdictions, additional legal criteria are required to resolve such a conflict. The classification of extraterritorial jurisdiction depending on the principles on which it is based also does not solve the problem, since some principles, such as protective or universal, in turn, require additional criteria in order to become a self-sufficient tool to overcome legal uncertainty. The author notes that the ability to exercise territorial jurisdiction within maritime areas, as a rule, determines the ability to exercise legislative and executive jurisdiction, which are also not absolute. The exercise of extraterritorial legislative or executive jurisdiction at sea is potentially permissible only on the basis of international law to solve a specific function, for example, law enforcement.DISCUSSION AND CONCLUSION. The main problem of the varieties of jurisdiction proposed by in- ternational legal science is that each of them only supplements each other, describing a possible choice, but not explaining why a particular choice should be preferred in case of conflict. It is obvious that current uncertainty has created some severe impacts upon the institution of law enforcement measures at sea as a result of the absence of standards for enforcement measures that could make a balance to the mechanism. Hence the law enforcer has to be cautious with a number of factors in deciding the implementation of law enforcement measures within the sea.